The Effect of Rise Husk Ash on Concrete Mixing Quality Formula - Hurul 'Ain; Alan Putranto; Betti Ses Eka Polonia; Ahmad Ravi (P3M Politeknik Negeri Banjarmasin, 2020)
The effect of the addition of rice husk ash (rice husk ash) to the K-175 formula quality concrete mixture, as an aggregate mixture to the concrete compressive strength test using a Compression Testing Machine to get the compressive strength value of concrete and can be used as an alternative material as an additional material in making concrete in improving the quality of building construction. The study uses K-175 concrete quality characteristics as a test material. Test object in the shape of a cube with a size of 15cm x 15cm. With 4 variations in levels of addition of rice husk ash by 0%, 1.5%, 3.5%, and 5% by weight of cement. The husk ash used is the husk ash that escaped the 2.36 mm filter size. From each type of mixture made 9 test specimens, every 3 specimens for the age of concrete 7 days, 14 days and 28 days. Concrete mortar design using ASTM method. With material sources using fine aggregate from the Pawan Ketapang River and coarse aggregate from Merak, Banten. Stages of implementation include examining the nature of aggregate materials, sample making, and testing of concrete compressive strength.